Market Access Bargaining in the Uruguay Round : Rigid or Relaxed Reciprocity? - Finger, Michael J. (The World Bank, 1999)
December 1999 - The Uruguay Round tariff negotiations did not achieve a country-by-country balancing of concessions given and concessions received. How governments bargained was determined less by their national interests than by the interests of their politically important industrial constituencies. How tightly are trade negotiators held to winning a dollar of concession for each dollar of concession granted? The outcome of the Uruguay Round tariff negotiations suggests that such constraints were not tight. None of the delegations interviewed by Finger, Reincke, and Castro had tried to calculate for themselves the extent of concessions received. And the surplus or deficit of concessions received (over concessions given) varied widely among countries. Measuring the percentage point dollar of concessions given and received (a percentage point dollar being a reduction of the tariff by one percentage point on